Accessibility to health services in the prison population in Colombia: a public health challenge - Luz Mery Mejía O; Jeniffer Hernández P (Universidad de Antioquia, 2010)
This article is the result of a product of a study elaborated with the aim of systematizing the available information related to the accessibility to the health services of the prison population in the penitentiary centers. To this end, we reviewed the literature and systematic collection of the academic available material in the principal university libraries in the city of Medellin, scientific databases and the web pages of national and international organizations that have dealt with this topic. The information was systematized considering some historical references to prisons and health, the record of experiences in some countries and the current regulations for health care in the prison population in the Colombian case. We conclude that although significant progress has been made to ensure health care for the prison population, in the prison there are still obstacles and limitations that infringe the right to health of this population. Likewise, it is evidenced that it has not been considered a public health problem in the country, which it is considered a challenge to incorporate it as such.